Ampel-Monitor Energiewende shows the pace of the energy transition must be accelerated significantly - Wolf-Peter Schill; Alexander Roth; Adeline Guéret (DIW Weekly Report, 2022)
The so-called traffic light coalition is facing a challenge: it has set ambitious energy policy targets, but can only achieve them if the pace of the energy transition is increased significantly. To contribute to the current energy policy debate, the Ampel-Monitor Energiewende (Monitor of the Traffic Light Coalition's Energy Transition Targets) was developed at DIW Berlin. Based on open data, the Ampel-Monitor Energiewende currently uses 15 indicators to compare the government targets for 2030 and beyond with developments and progress to date. For almost all indicators, there is a large gap between current trends and government targets, especially for renewable heat, electromobility, and green hydrogen. Moreover, the expansion pace of onshore and offshore wind power has recently lagged significantly behind what is necessary to achieve the 2030 targets. Concrete and far-reaching policy measures must be implemented in a timely manner for the targets to be achieved. The Ampel-Monitor Energiewende will continually monitor the success of the traffic light coalition's policies.
Keywords: Q42; Q48; 330; energy policy; monitoring; open data; Germany